Needs Analysis in Determining the Suitability of Interactive Infographic Learning Media in Elementary Schools - Raharjo, Makmum; Safitri, Erna Retna; Harlin (Universitas Pendidikan Ganesha, 2024)
Students' difficulties in visualizing learning material often cannot be explained only through text or static images. Apart from that, the lack of student involvement in traditional learning and changes in the demands of learning needs in the digital era, make the development of interactive infographic media important in the current digital context. This research aims to highlight the importance of needs analysis in determining suitable learning media, especially appropriate infographic media, to support learning in elementary schools. This research uses quantitative descriptive methods. The Guttman scale questionnaire is used to collect data on the needs of students, teachers, learning media, and learning objectives. The subjects involved in this research were students. The aspects measured include pedagogical, technical, cognitive, aesthetic, socio-cultural and evaluative aspects, which are then analyzed from questionnaire data to determine the most appropriate learning media. The results of the analysis show that the highest criteria are the pedagogical aspect, followed by the technical aspect, then the cognitive aspect, the aesthetic aspect, the socio-cultural aspect, and finally the evaluative aspect. This concludes the need to consider interactive infographic media that can improve the quality of learning. Implications of this research make significant contributions to the development of technology-based education at the elementary level.